Founding weaver ant queens (Oecophylla longinoda) increase production and nanitic worker size when adopting non-nestmate pupae - SINZOGAN, ANTONIO ALAIN KOFFI (My University, 2015)
Weaver ants (Oecophylla longinoda Latreille) are used commercially to control pest insects and for protein production. In this respect fast colony growth is desirable for managed colonies. Transplantation of non-nestmate pupae to incipient colonies has been shown to boost colony growth. Our objectives were to find the maximum number of pupae a founding queen can handle, and to measure the associated colony growth. Secondly, we tested if transplantation of pupae led to production of larger nanitic workers (defined as unusually small worker ants produced by founding queens in their first batch of offspring). Forty-five fertilized queens were divided into three treatments: 0 (control), 100 or 300 non-nestmatepupae transplanted to each colony. Pupae transplantation resulted in highly increased growth rates, as pupae were readily adopted by the queens and showed high proportions of surviving (mean = 76%). However, survival was significantly higher when 100 pupae were transplanted compared to transplantation of 300 pupae, indicating that queens were unable to handle 300 pupae adequately and that pupae require some amount of nursing. Nevertheless, within the 60-day experiment the transplantation of 300 pupae increased total colony size more than 10- fold whereas 100 pupae increased the size 5.6 fold, compared to control. This increase was due not only to the individuals added in the form of pupae but also to an increased per capita brood production by the resident queen, triggered by the adopted pupae. The size of hatching pupae produced by the resident queen also increased with the number of pupae transplanted, leading to larger nanitic workers in colonies adopting pupae. In conclusion, pupae transplantation may be used to produce larger colonies with larger worker ants and may thus reduce the time to produce weaver ant colonies for commercial purposes. This in turn may facilitate the implementation of the use of weaver ants.
Keywords: Biological control; Colony growth; Entomophagy; Nanitic worker size; Oecophylla; longinoda; Weaver ant farming